Modified percutaneous tracheostomy in patients with COVID-19. Issue 1 (14th December 2020) - Sun, Beatrice J; Wolff, Christopher J; Bechtold, Hannah M; Free, Dwayne; Lorenzo, Javier; Minot, Patrick R; Maggio, Paul G; Spain, David A; Weiser, Thomas G; Forrester, Joseph D
Abstract : Background: Patients hospitalized with COVID-19 are at risk of developing hypoxic respiratory failure and often require prolonged mechanical ventilation. Indication and timing to perform tracheostomy is controversial in patients with COVID-19. Methods: This was a single-institution retrospective review of tracheostomies performed on patients admitted for COVID-19 between April 8, 2020 and August 1, 2020 using a modified percutaneous tracheostomy technique to minimize hypoxia and aerosolization. Results: Twelve tracheostomies were performed for COVID-related respiratory failure. Median patient age was 54 years (range: 36–76) and 9 (75%) were male. Median time to tracheostomy was 17 days (range: 10–27), and 5 (42%) patients had failed attempts at extubation prior to tracheostomy. There were no intraprocedural complications, including hypoxia. Post-tracheostomy bleeding was noted in two patients. Eight (67%) patients have been discharged at the time of this study, and there were four patient deaths unrelated to tracheostomy placement. No healthcare worker transmissions resulted from participating in the tracheostomy procedure. Conclusions: A modified percutaneous tracheostomy is feasible and can be safely performed in patients infected with COVID-19. Level of evidence: Level V, case series.